Evaluasi Strategi Komunikasi Gerakan Memasyarakatkan Makan Ikan di Kabupaten Sleman - Winda Zanuanita Dhewi; Christina Rochayanti; Sigit Tri Pambudi (Jurnal Paradigma, 2019)
The movement to popularize eating fish (Gemarikan) national program is a government program to build awareness of individual nutrition and the collective community